Evaluation of effectiveness of central venous catheter related bloodstream infections in the antesty and reanimation intensive care units of the bundle (Annals of Medical Research, 2021)
Aim: The aim of this study is to evaluate the efficacy of prevention bundle study on central venous catheter-associated bloodstream infection (CLABSI) in the Anesthesia and Reanimation Intensive Care Unit (ICU) patients who have central venous catheter. Invasive vehicle related infections, especially CLABSIs, are one of the most difficult infections in ICUs. It has been reported that the use of proven interventions as a bundle to prevent infections associated with invasive tools is effective in reducing infection rates. Materials and Methods:The study was conducted interventionally between July and December 2017. Data, physician and nurse information form, CLABSI package tracking form, CLABSI package information test form, CVC insertion process observation form, bedside CLABSI package tracking form, and CLABSI package tracking form. Ethics committee permission was obtained for the study. Approval was obtained from nurses and doctors. The study was carried out in three stages. Number, Percentage, Chi-square, Fisher Exact Chi-square Test and Wilcoxon Test were used in the research.Results: The overall compatibility of ICUs for the CLABSI bundle was 61%, 65% and 70%, respectively. As a result of the Bundle study, CLABSI rates per 1000 catheter days were decreased, from 11.3 to 9.5 in ICU1, from 9.4 to 6.8 in ICU2, and from 17.1 to 10.6 in ICU3.Conclusion: As a result, it was seen that CLABSI precaution bundle study prepared with evidence based guidelines decreased infection rates. The bundle is recommended for use in intensive care units.
Keywords: Bundle; CLABSI; CVC; healthcare-related infection; invasive vehicle-related infection